Comparative Genomics Analysis of Two Different Virulent Bovine Pasteurella multocida Isolates - Huihui Du; Rendong Fang; Tingting Pan; Tian Li; Nengzhang Li; Qiang He; Rui Wu; Yuanyi Peng; Zeyang Zhou (International Journal of Genomics)
The Pasteurella multocida capsular type A isolates can cause pneumonia and bovine respiratory disease (BRD). In this study, comparative genomics analysis was carried out to identify the virulence genes in two different virulent P. multocida capsular type A isolates (high virulent PmCQ2 and low virulent PmCQ6). The draft genome sequence of PmCQ2 is 2.32 Mbp and contains 2,002 protein-coding genes, 9 insertion sequence (IS) elements, and 1 prophage region. The draft genome sequence of PmCQ6 is 2.29 Mbp and contains 1,970 protein-coding genes, 2 IS elements, and 3 prophage regions. The genome alignment analysis revealed that the genome similarity between PmCQ2 and PmCQ6 is 99% with high colinearity. To identify the candidate genes responsible for virulence, the PmCQ2 and PmCQ6 were compared together with that of the published genomes of high virulent Pm36950 and PmHN06 and avirulent Pm3480 and Pm70 (capsular type F). Five genes and two insertion sequences are identified in high virulent strains but not in low virulent or avirulent strains. These results indicated that these genes or insertion sequences might be responsible for the virulence of P. multocida, providing prospective candidates for further studies on the pathogenesis and the host-pathogen interactions of P. multocida.